Comparative Analysis of Local Government Systems in Western Europe: Legislative Frameworks and Organizational Models - Doctor, Chetna Arnaaz (Journal of Social Science and Humanities, 2026)
This research paper provides a comparative analysis of the organizational structures and legislative frameworks of local self- government systems in Western Europe, focusing on the Anglo-Saxon, French, and German models. The study examines the unique and shared characteristics of these models, the distribution of power within local government bodies, and the impact of legislative changes on local governance. Through an in-depth review of various legislative acts and their influence on local self-government, the paper highlights the evolution and current practices in local governance across different countries. The purpose of this article is to analyze the different models of local self-government in Western Europe, identify their unique and common features, and evaluate the impact of legislative frameworks on the functioning of local governance. This articles significance lies in its comprehensive analysis of various local government systems, which can provide valuable insights for policymakers, scholars, and practitioners interested in improving local governance through legislative reforms and structural adjustments. The study employs a comparative method, analyzing legislative acts and organizational structures of local self-government across several Western European countries. It involves a review of existing literature, legislative documents, and case studies to draw comparisons and assess the impact of different governance models. The paper suggests that understanding these models can offer valuable lessons for other regions aiming to enhance their local governance systems.